Adipose tissue at the nexus of systemic and cellular immunometabolism. Issue 5 (October 2016) - Kohlgruber, Ayano C.; LaMarche, Nelson M.; Lynch, Lydia
Highlights: Immunometabolism can be split into two main themes: whole-body metabolism and cellular bioenergetics. Adipose tissue is a prime example to illustrate immunometabolism as a whole. Immune cells resident in adipose tissue produce metabolism-altering molecules. Cell intrinsic metabolism dictates immune cell function, which in turn can alter systemic metabolism. Abstract: At the simplest interpretation of the word, Immunometabolism describes the intersection of the fields of immunology and metabolism. With rapidly growing interest in this field, the term has expanded, and now encompasses a variety of concepts and definitions shaped by an individual's scientific area of expertise, cell-type and tissue of interest, and biological approach. One scientist may be interested in investigating the intrinsic metabolic checkpoints that drive a M1 versus M2 macrophage response, while another may be interested in how macrophages affect systemic metabolism during obesity. Although both interests have very different foci, they both reflect the current interests in immunometabolism and studies over the last decade have uncovered new metabolic nodes that dictate the course of effector fate within cells, as well as an unexpected role for the immune system in controlling systemic metabolism. Thus, immunometabolism is at the frontier for many novel therapeutic targets to control both cell intrinsic and whole body metabolism in many diseases including cancer, diabetes, obesity, and sepsis among others. In this review, we hope to break down the word immunometabolism into two main themes: whole-body metabolism and cellular bioenergetics. In each instance we will focus on the adipose tissue and its resident immune cells to illustrate recent advances in both sectors of immunometabolism.